Enhancing Conceptual Understanding in Geometry through the Predict-Observe-Explain (POE) Model: A Quasi-Experimental Study in Secondary Education - Finanta Diva Sabila; Ahmad Yani T; Dona Fitriawan; Dede Suratman; Revi Lestari Pasaribu (STKIP Singkawang, 2026)
This study aims to determine the difference in the average conceptual understanding ability of students at SMP Negeri 8 Pontianak on flat-sided solid geometry material, particularly pyramids, between classes using the Predict-Observe-Explain (POE) model and Direct Instruction, as well as to determine the magnitude of the POE model's effect on students' conceptual understanding ability. This study uses a quantitative approach with a quasi-experimental research type in the form of a non-equivalent pretest-posttest control group design, involving 64 eighth-grade students at SMP Negeri 8 Pontianak. Data were collected through a conceptual understanding ability test and analyzed using an independent two-sample T-test and effect size. The results showed that there was a difference in conceptual understanding ability between students in both classes, with a value of . In addition, the POE model had a large effect on students' conceptual understanding ability with an effect size value of 0.9098. The superiority of the POE model in conceptual understanding is attributed to its capacity to trigger cognitive conflict through direct exploration and to facilitate meaningful concept reconstruction. Per-indicator analysis showed that the greatest advantage of students in the POE class was on the indicator of connecting various mathematical concepts, followed by the indicator of presenting concepts through multiple mathematical representations and the indicator of restating concepts. Conversely, on the indicator of applying concepts algorithmically, the achievement of both classes was relatively similar, with the Direct Instruction class obtaining a slightly higher percentage. These findings suggest that exploration-based approaches such as the POE model have the potential to be considered in the development of mathematics curricula more oriented toward the construction of conceptual understanding, particularly in solid geometry.Peningkatan Pemahaman Konsep dalam Geometri melalui Model Predict-Observe-Explain (POE): Studi Kuasi-Eksperimental pada Siswa SMPABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaan rata-rata kemampuan pemahaman konsep siswa SMP Negeri 8 Pontianak pada materi bangun ruang sisi datar, khususnya limas, antara kelas yang menggunakan model Predict Observe Explain (POE) dan kelas yang menggunakan Direct Instruction, serta mengetahui besar pengaruh model POE terhadap kemampuan pemahaman konsep siswa. Kajian ini menggunakan pendekatan kuantitatif dengan jenis penelitian quasi eksperimen berupa non-equivalent pretest posttest control group design, dengan melibatkan 64 siswa kelas VIII SMP Negeri 8 Pontianak. Data dikumpulkan melalui tes kemampuan pemahaman konsep dan dianalisis menggunakan uji T dua sampel independen serta effect size. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan pemahaman konsep antara siswa pada kedua kelas, dengan nilai Selain itu, model POE memberikan pengaruh yang besar terhadap kemampuan pemahaman konsep siswa dengan nilai effect size sebesar 0,9098. Keunggulan model POE dalam pemahaman konsep ini berkaitan dengan kemampuannya memicu konflik kognitif melalui eksplorasi langsung dan memfasilitasi rekonstruksi konsep secara bermakna. Adapun analisis per indikator menunjukkan bahwa keunggulan terbesar siswa pada kelas POE terdapat pada indikator mengaitkan berbagai konsep matematika, diikuti indikator menyajikan konsep dalam berbagai representasi matematis dan indikator menyatakan ulang konsep. Sebaliknya, pada indikator menerapkan konsep secara algoritma, capaian kedua kelas relatif serupa dan kelas Direct Instruction memperoleh persentase sedikit lebih tinggi. Temuan ini memberi implikasi bahwa pendekatan berbasis eksplorasi seperti model POE berpotensi menjadi pertimbangan dalam pengembangan kurikulum matematika yang lebih berorientasi pada konstruksi pemahaman konseptual, khususnya pada materi geometri ruang.Kata Kunci :Model Predict Observe Explain; Kemampuan Pemahaman Konsep; Bangun Ruang Sisi Datar